Mental Health in the Digital Era: Integrating the Teachings of Pancasila Values - Deswita, Nadya; Fauzi, M. Arif; Simanjuntak, Christin Eva; Barus, Sry Yanti; Nasution, Chindy Atika (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research investigates the integration of Pancasila values ??in improving the mental health of generation Z in Indonesia in the context of the digital era. In the era of globalization influenced by digital technology, responsible use of technology and guided by the values ??of Pancasila is important to ensure good mental health. This research uses qualitative analysis methods, especially literature analysis, as well as a case study approach to gain an in-depth understanding of the experiences of Generation Z individuals in using digital technology and its impact on their mental health. The research results highlight the importance of integrating Pancasila values ??in improving mental health, as well as the need for a holistic approach in overcoming generation Z's mental health challenges in the digital era. The practical implications of this research include the need for education about Pancasila values, responsible use of technology, and awareness of mental health in the digital era. It is hoped that this research can provide a basis for developing effective intervention programs in improving the mental health of generation Z in Indonesia. In the ever-growing digital era, the role of digital technology has become very significant in everyday life and has become a major force in global transformation. It is important for Indonesian citizens to consider the responsible integration of Pancasila values ??into mental health in the digital era.